Time code - Figgis, Mike; Stewart, Annie ([Culver City, CA : Columbia TriStar], 2002)
A behind-the-Hollywood-scenes drama in which four separate cameras follow the lives of a diverse group of L.A. players as the curtain unfolds in real time with no edits and no retakes, building toward a disturbing climax
Writer, Mike Figgis
cast: Saffron Burrows, Sama Hayek, Stellan Skarsgard
VCD format
Keywords: Erotic films; Sex in motion pictures